Laser‐Induced Graphene Piezoresistive Sensors Synthesized Directly on Cork Insoles for Gait Analysis. Issue 12 (9th November 2020) - Carvalho, Alexandre F.; Fernandes, António J. S.; Martins, Rodrigo; Fortunato, Elvira; Costa, Florinda M.
Abstract: Monitorization of gait‐related parameters is of the utmost importance to prevent complications in several diseases, ensuring affordable healthcare for the growing amount of chronic, lifestyle‐related diseases and also for improving motion performance. Sensorized insoles allow to both pressure data and gait timings to be extracted non‐intrusively in a point of care paradigm. Laser‐induced graphene (LIG) offers a path to the integration of sensors in different kinds of materials, including cork, a common insole material. In this work, piezoresistive sensors are developed by providing conductivity to natural cork and agglomerate cork through the direct synthesis of LIG by UV irradiation. Highly isotropic conductive LIG regions with less than 100 Ω sq −1 are patterned and their piezoresistive response for up to 1132 kPa is assessed with sensitivities up to 0.02 kPa −1 . A low‐cost prototype insole is devised and tested, proving the potential of this kind of functional cork as a green alternative for gait analysis platforms. Abstract : The monitorization of the feet palm pressure is of the utmost importance in rehabilitation and disease prevention. Here, the fabrication of laser‐induced graphene directly onto cork insoles is presented and their performance as pressure sensors is evaluated, opening the path for a green sensing platform.